Hypoxic breathing produces more intense hypoxemia in elderly women than in elderly men - Zhao, Jinfeng; Ding, Yanfeng; Kline, Geoffrey P.; Zhou, Zhengyang; Mallet, Robert T.; Shi, Xiangrong (Frontiers in Physiology, 2022)
Background: Brief hypoxic exposures are increasingly applied as interventions for aging-related conditions. To optimize the therapeutic impact of hypoxia, knowledge of the sex-related differences in physiological responses to hypoxia is essential. This study compared hypoxia-induced hypoxemic responses in elderly men and women. Methods: Seven elderly men (70.3 ± 6.0 years old) and nine women (69.4 ± 5.5 years old) breathed 10% O2 for 5 min while arterial (SaO2; transcutaneous photoplethysmography) and cerebral tissue O2 saturation (ScO2; near-infrared spectroscopy), ventilatory frequency, tidal volume, minute-ventilation, and partial pressures of end-tidal O2 (PETO2) and CO2 (mass spectrometry) were continuously monitored. Cerebral tissue oxygen extraction fraction (OEF) equaled (SaO2–ScO2)/SaO2. Results: During 5 min hypoxia SaO2 fell from 97.0 ± 0.8% to 80.6 ± 4.6% in the men and from 96.3 ± 1.4% to 72.6 ± 4.0% in the women. The slope ΔSaO2/min was steeper in the women than the men (−4.71 ± 0.96 vs. −3.24 ± 0.76%/min; p = 0.005). Although SaO2 fell twice as sharply per unit decrease in PETO2 in the women than the men (−1.13 ± 0.11 vs. −0.54 ± 0.06%/mmHg; p = 0.003), minute-ventilation per unit hypoxemia increased less appreciably in the women (−0.092 ± 0.014 vs. −0.160 ± 0.021 L/min/%; p = 0.023). OEF fell with hypoxia duration in the women, but remained stable in the men. Conclusion: During 5 min hypoxic breathing, elderly women experience more intense hypoxemia and reduced chemoreflex sensitivity vs. their male counterparts, which may lower OEF stability in women despite augmented O2 dissociation from hemoglobin during hypoxia. These sex-related differences merit attention when implementing brief hypoxic exposures for therapeutic purposes.